2019
DOI: 10.1002/jcb.29274
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of microRNA‐129‐5p increases the risk of intervertebral disc degeneration by promoting the apoptosis of nucleus pulposus cells via targeting BMP2

Abstract: miR-129-5p is implicated in many diseases, such as laryngeal cancer and breast cancer. In this study, we studied the mechanism underlying the role of BMP2 in intervertebral disc degeneration (IDD). We used a luciferase assay system to determine the relationship between BMP2 and miR-129-5 expression. In addition, Western blot and real-time PCR were used to confirm the regulatory relationship between miR-129-5p and its targets, while flow cytometry was used to evaluate the effect of miR-129-5p on the apoptosis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…In addition to its association with tumorigenesis, miR-129-5p was implicated in other diseases. A study by Yang et al suggested that dysregulation of miR-129-5p might contribute to the development of intervertebral disc degeneration by targeting bone morphogenetic protein 2 (BMP2) expression [25]. In patients with intervertebral disc degeneration, miR-129-5p was downregulated along with BMP2 upregulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to its association with tumorigenesis, miR-129-5p was implicated in other diseases. A study by Yang et al suggested that dysregulation of miR-129-5p might contribute to the development of intervertebral disc degeneration by targeting bone morphogenetic protein 2 (BMP2) expression [25]. In patients with intervertebral disc degeneration, miR-129-5p was downregulated along with BMP2 upregulation.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, miR-129-5p has received considerable attention as a driver of Alzheimer' s disease [23], osteogenesis [24], and intervertebral disk degeneration [25]. Furthermore, miR-129-5p was reported to be involved in the tumorigenesis of gastric [26][27][28], pancreatic [29], laryngeal [30], prostate [31], and lung cancer [32] as well as of hepatocellular carcinoma [33].…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, miRNA also regulates the expression and function of circRNA [ 17 ]. Growing proofs have unveiled that both miRNAs [ [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] ] and circRNAs [ [20] , [21] , [22] , [23] , [24] , [25] , [26] ] play a significant regulatory role in the occurrence and progression of IDD. Mechanistically, the circRNAs-mediated the pathological process of IDD is miRNA dependent, which acts as competitive endogenous RNA (ceRNA) to interact with miRNAs [ [20] , [21] , [22] , [23] , [24] , [25] , [26] ].…”
Section: Introductionmentioning
confidence: 99%
“… 7 Furthermore, miR-129-5p can enhance cell viability, while inhibiting apoptosis of NP cells, thus contributing to the alleviation of IDD development by targeting BMP2. 8 Initial prediction results from the starBase database highlight the presence of miR-129-5p binding sites in the 3′-untranslated region (3′-UTR) of leucine-rich α2-glycoprotein1 (LRG1), a pleiotropic protein belonging to the LRG family that plays a pathogenic role in multiple degenerative diseases; for instance, accumulation of LRG is thought to be responsible for the neurodegeneration of patients with Parkinson’s disease. 9 In addition, up-regulated expressions of LRG have been previously reported to be associated with granulomatous tissue formation, cartilage degeneration, and bone destruction in the event of rheumatoid arthritis.…”
Section: Introductionmentioning
confidence: 99%